Disruption of gamete fusion alters the sperm-egg ratio at gamete interaction - Eva Stickler; Matteo Avella (Journal of Translational Medicine)
Abstract Background The mechanisms enabling sperm to locate unfertilized eggs within the fallopian tubes remain a subject of debate in reproductive biology. Previous studies using polytocous mammals observed a 1:1 sperm-egg ratio within the ampulla at the time of fertilization. From these observations, it is hypothesized that this mechanism could be linked to sperm-egg fusion, such that unfertilized eggs may attract sperm until fusion occurs, whereupon the attraction ceases. Methods To test this, fertile male mice were mated with infertile homozygous Cd9 Null females, whose eggs cannot fuse with sperm, leading to the accumulation of supernumerary sperm in the perivitelline space. Fertile heterozygous Cd9 Het females, were used as controls. Results The results revealed that both Cd9 Null and Cd9 Het females ovulated similar numbers of eggs (6.53 ± 0.61 vs. 5.50 ± 0.53 eggs/ampulla). The majority of eggs produced by Cd9 Het females were fertilized by one single sperm, without any additional sperm found bound to the zona or within the perivitelline space. In contrast, most of the eggs ovulated by Cd9 Null females either showed an accumulation of supernumerary sperm within in the perivitelline space or showed no sperm bound to the zona nor present within the perivitelline space. Conclusions These findings indicate that genetic ablation of Cd9 leads to an imbalance in the 1:1 sperm-egg ratio observed within the ampulla. This information may set the foundation for future studies with the aim to identify the specific mechanisms that sperm use to locate unfertilized eggs and whether they become ineffective when gamete fusion is prevented.